Bahasa Inggris - Andriani, Diyah Iis (Universitas Putera Batam, 2023)
This research analyzed the language codes used in the song lyrics of an Indonesian group called Un1ty. The purposes of this research were to identify the types of code-switching and code-mixing and the reasons for using the codes in the lyrics of the songs. This research used descriptive qualitative method and the data were analyzed using the theory of Hoffman (1991) to investigate the types of code switching and code mixing and to find the reasons of using the codes in the song lyrics. The results of this research indicated that there were 31 data points. For the type of code-switching, the researchers found that there were 21 data, namely 5 types of intra-sentential switching, 15 inter-sentential switching, and 1 tag switching. Meanwhile, there were 9 data for code-mixing, 8 for intra-sentential mixing and 1 for change pronunciations. Furthermore, for the reasons, there are 13 being empathic about something (express solidarity), 4 talking about particular topic, 1 expressing group identity, 8 intention of clarifying the speech content for interlocutors, 1 repetition used for clarification and 3 interjection (insert sentence fillers or sentence connectors).